2007
DOI: 10.1002/mrc.2005
|View full text |Cite
|
Sign up to set email alerts
|

1H and 13C NMR assignments for two new angular furanocoumarin glycosides from Peucedanum praeruptorum

Abstract: Two novel angular-type furanocoumarin glycosides, peucedanoside A (1) and peucedanoside B (2), along with a known compound apterin (3), were isolated from the roots of Peucedanum praeruptorum Dunn. Their chemical structures were determined by MS, NMR spectroscopy and chemical analysis. Complete assignments of the 1H and 13C NMR spectroscopic data were achieved by 1D and 2D NMR experiments including DEPT, HSQC, HMBC and ROESY.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…29 The Cprenyl group is also found cyclised onto an ortho-phenol to form extensive ranges of furanoflavones and pyranoflavones. 30 One may speculate that the isomeric furanoflavone 1 and pyranoflavone 2 (also atalantoflavone 16 ) arise through 5-exo and 6-endo cyclisations of a common oxidised derivative of 4, such as 8-(3,3-dimethyloxiranylmethyl)-4′,5,7-trihydroxyflavone. Retamasin A and retamasin B, previously reported in R. raetam, 16 are furanoflavones which may also derive from 4.…”
Section: Resultsmentioning
confidence: 99%
“…29 The Cprenyl group is also found cyclised onto an ortho-phenol to form extensive ranges of furanoflavones and pyranoflavones. 30 One may speculate that the isomeric furanoflavone 1 and pyranoflavone 2 (also atalantoflavone 16 ) arise through 5-exo and 6-endo cyclisations of a common oxidised derivative of 4, such as 8-(3,3-dimethyloxiranylmethyl)-4′,5,7-trihydroxyflavone. Retamasin A and retamasin B, previously reported in R. raetam, 16 are furanoflavones which may also derive from 4.…”
Section: Resultsmentioning
confidence: 99%
“…Phytochemical and pharmacological studies showed that angular-type pyranocoumarins are the major constituents of this plant [3][4][5][6][7][8][9], and these compounds have various beneficial effects such as anti-inflammatory [10][11][12], antiasthma [13], chemopreventive [14], smooth muscle relaxant [15], neuroprotective [16], and anti-osteoclastogenic properties [17].…”
Section: Introductionmentioning
confidence: 99%
“…The structures of the isolates were determined spectroscopically using one-dimensional (1D)-and two-dimensional (2D)-nuclear magnetic resonance (NMR) analysis. All the compounds (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) were evaluated for multidrug resistance (MDR) reversal and anti-inflammatory activity against multidrug resistant MES-SA/Dx5 cancer and lipopolysaccharide (LPS)-stimulated RAW 264.7 cells. Here, we 1 Hz, H-4′′′), 1.81 (3H, m, H-5′′′)] were observed from the 1 H-NMR spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…So far, more than 50 coumarins have been isolated from Peucedani Radix, including (±)‐praeruptorin A, (±)‐praeruptorin B, (+)‐praeruptorin A, (+)‐praeruptorin B, (+)‐praeruptorin E, etc 7–10. Most of these coumarins belong to angular‐type pyranocoumarin, which has a khellactone skeleton with different substituents at the C‐3′ and C‐4′ positions.…”
mentioning
confidence: 99%